2016
DOI: 10.1155/2016/8191659
|View full text |Cite
|
Sign up to set email alerts
|

The Value of ABCD2F Scoring System (ABCD2 Combined with Atrial Fibrillation) to Predict 90-Day Recurrent Brain Stroke

Abstract: Background. The ABCD2 score is now identified as a useful clinical prediction rule to determine the risk for stroke in the days following brain ischemic attacks. Aim. The present study aimed to introduce a new scoring system named “ABCD2F” and compare its value with the previous ABCD2 system to predict recurrent ischemic stroke within 90 days of the initial cerebrovascular accident (CVA). Methods. 138 consecutive patients with the final diagnosis of ischemic CVA or TIAs who referred to emergency ward of Rasoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Atrial fibrillation is a known risk factor for cerebrovascular ischemic events. However, validation studies of post-TIA risk scores have not found an increased predictive stroke risk accuracy by taking atrial fibrillation into account [ 26 , 27 ]. In our study, when comparing proportions of atrial fibrillation between low- and medium- to high-risk patients, we did not find significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation is a known risk factor for cerebrovascular ischemic events. However, validation studies of post-TIA risk scores have not found an increased predictive stroke risk accuracy by taking atrial fibrillation into account [ 26 , 27 ]. In our study, when comparing proportions of atrial fibrillation between low- and medium- to high-risk patients, we did not find significant differences.…”
Section: Discussionmentioning
confidence: 99%